Assessment of family physicians' knowledge of childhood autism. Issue 4 (1st December 2017) - Salama, Hend Mikhail
Abstract : Objective: This study aimed to assess the knowledge of family physicians regarding childhood autism. Methods: The study is a one-way cross-sectional descriptive study, conducted between January and March 2017. The study involved 70 family physicians who were working and/or studying for a master degree in the School of Medicine, Suez Canal University. The researcher collected the sociodemographic characteristics, and then the participants completed the Knowledge about Childhood Autism among Healthcare Workers (KCAHW) questionnaire. Results: The total KCAHW score was 11.2 ± 3.5 (mean ± standard deviation), the domain with the highest score was domain 1 (5.6 ± 1.8), and family physicians with previous experience had a higher mean score than physicians with no previous experience (12.9 ± 2.7 and 10.7 ± 3.5 respectively). In addition, there was a significant positive correlation between the mean KCAHW score and both the duration of practicing and earlier experience of autism. Conclusion: There is a lack of knowledge of autism among family physicians; they need more training on autism to increase their awareness to improve early detection and intervention so as to improve the quality of life and care of children with autism.